2018
DOI: 10.1111/dom.13387
|View full text |Cite
|
Sign up to set email alerts
|

Islet stress, degradation and autoimmunity

Abstract: β‐cell destruction in type 1 diabetes (T1D) results from the effect of inflammation and autoimmunity. In response to inflammatory signals, islet cells engage adaptive mechanisms to restore and maintain cellular homeostasis. Among these mechanisms, the unfolded protein response (UPR) leads to a reduction of the general protein translation rate, increased production of endoplasmic reticulum chaperones and the initiation of degradation by activation of the ER associated degradation pathway (ERAD) in which newly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…TNF-α is a key pro-inflammatory factor, located within the HLA III region in chromosome 6p21,and has been related to several human autoimmune diseases like rheumatoid arthritis, pernicious anemia, diabetes mellitus, and its microvascular complications like DN and DR [1,46]. Previous studies have demonstrated that TNF-α has been regarded as an important factor in obesity-associated insulin resistance [47,48] 51]. There were several studies concentrated on TNF-α-308 G/A polymorphism, with substitution of guanine for adenine in the promoter region, which access to a higher rate of TNF-α gene transcription compared with the G allele in vitro expression studies [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a key pro-inflammatory factor, located within the HLA III region in chromosome 6p21,and has been related to several human autoimmune diseases like rheumatoid arthritis, pernicious anemia, diabetes mellitus, and its microvascular complications like DN and DR [1,46]. Previous studies have demonstrated that TNF-α has been regarded as an important factor in obesity-associated insulin resistance [47,48] 51]. There were several studies concentrated on TNF-α-308 G/A polymorphism, with substitution of guanine for adenine in the promoter region, which access to a higher rate of TNF-α gene transcription compared with the G allele in vitro expression studies [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…During insulitis, proinflammatory cytokines released by infiltrating immune cells disrupt ER homeostasis, triggering the unfolded protein response. This adaptive phase is believed to play a critical role in the development of IA by promoting the generation of neoantigens and activating inflammatory responses [84]. Furthermore, ER stress induces translational errors, giving rise to defective ribosomal products of insulin that are highly immunogenic and targeted by T cell autoreactivity in type 1 diabetes [85].…”
Section: Crosstalk Between Early-life Factors and Pancreatic Beta Cellsmentioning
confidence: 99%
“…Interestingly, the virally transformed HEK293T was most prominent in extracellular HSP90α. Prominent representation by GRP78 in extracellular HSP complexes is significant with regard to a multi-modal influence on tumorigenesis and as the hub of the translational ER stress response (Ghaderi et al 2018;Steiner et al 2017;Thomaidou et al 2018). Interestingly, the clearest differentiation of HSP content was seen for distribution of inducible HSP70-1/2; while abundant in HEK293T, PSMs were not detected in equivalent eHSP of U87.…”
Section: Proteomic Analysismentioning
confidence: 99%